Effect Western Medicines Combined With Nao-Xue-Shu in Patients With Hypertensive Intracerebral Hemorrhage: A Network Meta-Analysis - Mei, Li; Fengqun, Mu; Xiaozhuo, Liu; Qing, Wang; Mingming, Fan; Zhengyao, Zuo; Dongpo, Su; Qian, Han; Tong, Chen (Frontiers in Pharmacology, 2022)
Purpose: To explore the efficacy of nimodipine, nifedipine, and edaravone(EDA) combined with Nao-Xue-Shu in patients with hypertensive intracerebral hemorrhage (HICH) and to determine the best western medicine combined with Nao-Xue-Shu for treating HICH patients using a ranking method. Methods: After a comprehensive search of the China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP information database, Chinese Biomedical Database (CBM), PubMed, Embase, and Cochrane Library databases from the database establishment December 31, 2021, data extraction and quality assessment were conducted for the included articles. The primary outcome measure was the effectiveness after treatment. Secondary outcome measures were after-treatment the National Institutes of Health Stroke Scale (NIHSS) scores, hematoma volume, perihematoma edema volume, and inflammatory factor expression levels. Statistical analyses were performed using Stata 16.0 and RevMan 5.3.0 software. Results: We included 19 randomized controlled trials (RCTs) and six non-RCTs. The effective rate after treatment was ranked from the best to the worst as follows: routine cure measure (RCM)+nifedipine+Nao-Xue-Shu, RCM+EDA+Nao-Xue-Shu, RCM+Nao-Xue-Shu, RCM+nimodipine+Nao-Xue-Shu, RCM+EDA, and RCM. The post-treatment NHISS scores from lowest to highest were as follows: RCM+EDA+Nao-Xue-Shu, RCM+nifedipine+Nao-Xue-Shu, RCM+EDA, RCM+nimodipine+Nao-Xue-Shu, RCM+Nao-Xue-Shu, RCM+Nao-Xue-Kang, and RCM. The post-treatment hematoma volume from minimum to maximum was as follows: RCM+EDA+Nao-Xue-Shu, RCM+nimodipine+Nao-Xue-Shu, RCM+nifedipine+Nao-Xue-Shu, RCM+ Nao-Xue-Shu, RCM+ Nao-Xue-Kang, and RCM. The post-treatment perihematoma edema volume from minimum to maximum was as follows: RCM+EDA+Nao-Xue-Shu, RCM+nifedipine+Nao-Xue-Shu, RCM+nimodipine+Nao-Xue-Shu, RCM+Nao-Xue-Shu, and RCM. For inflammatory factor expression levels after treatment, IL-6 concentration levels after treatment from lowest to highest were as follows: RCM+Nao-Xue-Shu, RCM+nifedipine+Nao-Xue-Shu, RCM+nimodipine+Nao-Xue-Shu, RCM+EDA+ Nao-Xue-Shu, and RCM. TNF-α concentration levels after treatment from lowest to highest was as follow: RCM+nimodipine+Nao-Xue-Shu, RCM+nifedipine+Nao-Xue-Shu, RCM+Nao-Xue-Shu, and RCM. Conclusions: Nao-Xue-Shu combined with nifedipine showed better effectiveness after treatment in HICH patients compared with the other combinations. Nao-Xue-Shu combined with edaravone was more effective for improving neurological function and reducing both hematoma and edema volumes around the hematoma compared with the other combinations. However, Nao-Xue-Shu alone or Nao-Xue-Shu combined with nimodipine may be more effective for reducing proinflammatory factor expression.